Increasing Student Interest in Interactive Multimedia Product Creation Subject through Scratch-Based Learning Media - Hana Romauli Sipahutar; Nurcahya Pradana Taufik Prakisya; Rosihan Ari Yuana (Journal of Informatics and Vocational Education, 2024)
Engaging students is essential in education. If students are interested in a subject, they will study it repeatedly, driven by their intrinsic motivation to achieve a goal. However, one of the schools, SMK N 1 Demak, has experienced problems with students' interest in learning. A teacher stated that during lessons for the "Making Interactive Multimedia Products" subject, students were often unfocused and did not pay attention, which is a characteristic of a lack of interest. This study aims to design learning media using the Scratch application to increase the interest of class XII students in making interactive multimedia products at SMK Negeri 1 Demak. The data collection techniques used were interviews and questionnaires. Data validity was ensured using construct validity techniques, while data analysis was performed using comparative descriptive and critical analysis techniques. The research procedure followed the ADDIE model. At the beginning of the application development, the developer consulted with subject and media experts. The measurement instruments were validated by an educational expert. The analysis of the results used descriptive percentages. The findings showed that the application of Scratch multimedia successfully increased students' interest in making interactive multimedia products in the class XII multimedia program at SMK Negeri 1 Demak.